Can the commons be temporary? The role of transitional commoning in post-quake Christchurch. Issue 4 (3rd April 2019) - Dombroski, Kelly; Diprose, Gradon; Boles, Irene
ABSTRACT: In recent work on commons and commoning, scholars have argued that we might delink the practice of commoning from property ownership, while paying attention to modes of governance that enable long-term commons to emerge and be sustained. Yet commoning can also occur as a temporary practice, in between and around other forms of use. In this article we reflect on the transitional commoning practices and projects enabled by the Christchurch post-earthquake organisation Life in Vacant Spaces, which emerged to connect and mediate between landowners of vacant inner city demolition sites and temporary creative or entrepreneurial users. While these commons are often framed as transitional or temporary, we argue they have ongoing reverberations changing how people and local government in Christchurch approach common use. Using the cases of the physical space of the Victoria Street site "The Commons" and the virtual space of the Life in Vacant Spaces website, we show how temporary commoning projects can create and sustain the conditions of possibility required for nurturing commoner subjectivities. Thus despite their impermanence, temporary commoning projects provide a useful counter to more dominant forms of urban development and planning premised on property ownership and "permanent" timeframes, in that just as the physical space of the city being opened to commoning possibilities, so too are the expectations and dispositions of the city's inhabitants, planners, and developers.